Teaching Medical Informatics to Medical Students in the Federal Republic of Germany - Michaelis, J. (Methods of Information in Medicine, 1989)
The medical curriculum in the Federal Republic of Germany (FRG) is regulated by federal legislation. Medical informatics is part of this curriculum and is therefore taught by all 27 medical faculties in the FRG, 24 of which have related departments. The teaching situation in general and the specific approach at the author´s department are described.
Keywords: Medical Informatics Curriculum; Attitudes towards Computers; Expert Systems; Drug Interaction; Statistical Programs